Understanding the Research Evolution, Knowledge Structure, and Trends of Augmented Reality–Supported Problem-Based Learning: A Bibliometric Perspective - Lintang Auliya Kurdiati; Sabar Nurohman (Universitas Lambung Mangkurat, 2026)
his study systematically maps the intellectual structure, developmental trajectory, and emerging directions of Augmented Reality–Supported Problem-Based Learning (AR–PBL) research. Guided by five research questions, it examines publication growth patterns, identifies influential authors, institutions, and journals, uncovers major thematic clusters, analyzes keyword interconnections, and detects emerging research fronts. A bibliometric and network analysis was conducted on Scopus-indexed publications from 2015 to 2025, integrating PRISMA-based screening with Biblioshiny and VOSviewer visualization techniques. The results indicate a steady increase in AR–PBL publications over the past decade, reflecting expanding scholarly attention. Influential contributions are concentrated among a limited group of authors and institutions, while several core journals serve as primary outlets. Co-citation and conceptual structure analyses reveal dominant thematic clusters centered on pedagogical design, augmented reality applications, learner engagement, and system implementation. Keyword co-occurrence patterns demonstrate strong interconnections between AR technology and PBL pedagogy, yet limited integration with advanced computational approaches. Emerging theme analysis shows that areas such as learning analytics, artificial intelligence, and adaptive instructional systems remain underexplored. Overall, AR–PBL has evolved into a multi-clustered but unevenly integrated research domain, highlighting the need for stronger theoretical coherence, system-level integration, and pedagogical innovation in future studies.